2020
DOI: 10.1111/dme.14349
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial factors associated with a current depressive episode in diabetes: the ELSA‐Brasil study

Abstract: Aims Depression is more prevalent in people with diabetes, and is associated with worse diabetes outcomes. Depression in diabetes is more treatment resistant, and as underlying mechanisms are unknown, development of more effective treatment strategies is complicated. A biopsychosocial model may improve our understanding of the pathophysiology, and therewith help improving treatment options. Methods Diabetes was diagnosed according to American Diabetes Association (ADA) criteria and a current depressive episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Indeed, the level of depression symptoms in young diabetics in our study can be classified as mild depression. Many sources report that the prevalence of depression among diabetics type 1 and type 2 is higher compared to the people without diabetes (Gendelman et al, 2009;van Duinkerken et al, 2020). At the same time, we found that adolescents without diabetes show significantly higher levels of depressive symptoms.…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, the level of depression symptoms in young diabetics in our study can be classified as mild depression. Many sources report that the prevalence of depression among diabetics type 1 and type 2 is higher compared to the people without diabetes (Gendelman et al, 2009;van Duinkerken et al, 2020). At the same time, we found that adolescents without diabetes show significantly higher levels of depressive symptoms.…”
Section: Discussionsupporting
confidence: 64%
“…We read with great interest the findings of a cross-sectional analysis of ELSA-Brasil data by Van Duinkerken et al 1 The results of this study confirm that there are numerous biological, psychological and social correlates of depressive episodes in people living with diabetes. The authors concluded that a current depressive episode in the presence of diabetes was related more to biological than to psychosocial factors, compared with the absence of diabetes.…”
Section: Comment On Van Duinkerken Et Al Biopsychosocial Factors Asssupporting
confidence: 70%
“…In comparison with Humalog mix 25, Xultophy can bring better glucose variability with only one injection. The second is psycho-perspective [23]. The case feels easy because of a less anxious episode for hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%